Development of stress-strain models for glass fiber reinforced polymer composites confined sustainable concrete made with natural and recycled aggregates - Yooprasertchai, Ekkachai; Saingam, Panumas; Hussain, Qudeer; Khan, Kaffayatullah; Ejaz, Ali; Suparp, Suniti (My University, 2024)
This study addresses the mechanical limitations of concrete fabricated with recycled brick and concrete as partial replacement of coarse aggregates, which exhibit inferior strength and stiffness compared to those with natural aggregates. To rectify this, a cost-effective approach involving low-cost glass fiber-reinforced polymer composites (LOC-GFRP) is proposed. The key parameters considered were the plain concrete compressive strength and the quantity of LOC-GFRP layers. The compressive strength of LOC-GFRP-confined concrete increased with the number of layers, with greater improvements observed in lower-strength plain concrete. Moreover, the improvement in ultimate strain was more significant than the improvement in compressive strength. The compressive strength and ultimate strain were improved by 271% and 478%, respectively. LOC-GFRP confinement resulted in a bilinear compressive stress vs. strain response, showcasing increased ductility and strength with more LOC-GFRP layers. The study evaluated various existing analytical expressions for fiber-reinforced polymers but found them inadequate in predicting parameters accurately. As a result, nonlinear regression analysis was carried out to propose expressions for predicting compressive strength and ultimate strain of LOC-GFRP-confined concrete for different aggregate types. The calculated coefficient of determination values ≥ 0.90 confirmed the good correlation among experimental and predicted values.
Keywords: Axial compression; Compressive strength; Recycled aggregates; Stress-strain models; Sustainable concrete; Ultimate strain